ИЗУЧЕНИЕ МЕТАМОРФОЗА КЛЕЩЕЙ ЧЕСОТОЧНОГО ЗУДНЯ SARCOPTES SCABIEI КАРАКУЛЬСКИХ ОВЕЦ - Бобоназаров, Г.Я. (Actual problems and prospects of the study of the fauna, 2024)
The article presents the results of a study of the metamorphosis of scabies mites Sarcoptes scabiei in Karakul sheep. In experiments, the life cycle of development of scabies mites S. Scabiei in Karakul sheep from eggs to adults is 15-16 days, which is less than 2-3 and 5 days in other regions of the world studied. This is explained by the presence of favorable conditions for the development of scabies mites in these southern regions of the republic